DEVELOPMENT OF MOVEMENT OF DISABLED CHILDREN BY MEANS WITH THE HELP OF GYMNASTICS - Xolmatov Nizomjon Umarjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The results and lessons learned by the experiments delivered on the problems and solutions of preparing deaf children and children who have not fair hearing for social life basing on the effective innovative technologies implementation have discussed in this article. Moreover, taking into consideration the necessary comprehension for socialization of deaf and fair hearing children as well the effective ways and technologies of formulating children’s skills have revealed.